2018
DOI: 10.1093/nar/gky451
|View full text |Cite
|
Sign up to set email alerts
|

The archaeal ATPase PINA interacts with the helicase Hjm via its carboxyl terminal KH domain remodeling and processing replication fork and Holliday junction

Abstract: PINA is a novel ATPase and DNA helicase highly conserved in Archaea, the third domain of life. The PINA from Sulfolobus islandicus (SisPINA) forms a hexameric ring in crystal and solution. The protein is able to promote Holliday junction (HJ) migration and physically and functionally interacts with Hjc, the HJ specific endonuclease. Here, we show that SisPINA has direct physical interaction with Hjm (Hel308a), a helicase presumably targeting replication forks. In vitro biochemical analysis revealed that Hjm, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…We also characterized Tbar-aLhr2 as a monomeric DNA/RNA helicase able to process DNA:RNA and RNA:RNA duplexes (Figure S4 & Figure 7, left panels). Interestingly, we highlighted that the in vitro unwinding and annealing activities of Tbar-aLhr2 differ drastically from those of Hel308, described as a DNA helicase involved in DNA repair [35,44]. Indeed, we showed that while Tbar-aLhr2 is more prone to anneal nucleic strands than to unwind them, Paby-Hel308 unwinds 3 DNA:DNA homoduplexes but does not form them from ssDNA molecules (Figure 7).…”
Section: Discussionmentioning
confidence: 93%
“…We also characterized Tbar-aLhr2 as a monomeric DNA/RNA helicase able to process DNA:RNA and RNA:RNA duplexes (Figure S4 & Figure 7, left panels). Interestingly, we highlighted that the in vitro unwinding and annealing activities of Tbar-aLhr2 differ drastically from those of Hel308, described as a DNA helicase involved in DNA repair [35,44]. Indeed, we showed that while Tbar-aLhr2 is more prone to anneal nucleic strands than to unwind them, Paby-Hel308 unwinds 3 DNA:DNA homoduplexes but does not form them from ssDNA molecules (Figure 7).…”
Section: Discussionmentioning
confidence: 93%
“…The damages at the stalled replication forks may be repaired by translesion DNA synthesis, BER, MMR, or HR in different phases of cell cycle (Jones and Petermann, 2012). We have recently proposed a role of Hjc in repair of stalled replication fork in concert with Hjm and PINA (Zhai et al, 2018). The inhibition of Hjc activity by phosphorylation at S34 might avoid HJ cleavage and stalled replication fork collapse.…”
Section: Discussionmentioning
confidence: 99%
“…DNA replication fork is usually blocked by a lesion. The stalled replication fork would be reversed to a HJ DNA by proteins such as Hjm and/or PINA (PIN domain-containing ATPase), followed by the recruitment of Hjc (Zhai et al, 2018). Phosphorylation states of Hjc might control different repair pathways: Non-phosphorylated Hjc would cleave the HJ forming a DSB which would be repaired by HR; phosphorylated Hjc at S34 would not cleave the HJ and the lesion might be repaired by mismatch repair (MMR) or base excision repair (BER).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, different KH domains in the same protein may have different sequence preferences and affinity, such as the four KH domains in KSRP ( 17 ) and the 14 domains in vigilin ( 18 ). In addition to nucleic acid binding, the KH domain in PINA mediates the interactions of PINA with Hjm and Hjc and regulates the hexameric assembly of PINA ( 19 ).…”
mentioning
confidence: 99%